Multi-Task Supervised Alignment Pre-Training for Few-Shot Multimodal Sentiment Analysis - Junyang Yang; Jiuxin Cao; Chengge Duan (Applied Sciences)
Few-shot multimodal sentiment analysis (FMSA) has garnered substantial attention due to the proliferation of multimedia applications, especially given the frequent difficulty in obtaining large quantities of training samples. Previous works have directly incorporated vision modality into the pre-trained language model (PLM) and then leveraged prompt learning, showing effectiveness in few-shot scenarios. However, these methods encounter challenges in aligning the high-level semantics of different modalities due to their inherent heterogeneity, which impacts the performance of sentiment analysis. In this paper, we propose a novel framework called Multi-task Supervised Alignment Pre-training (MSAP) to enhance modality alignment and consequently improve the performance of multimodal sentiment analysis. Our approach uses a multi-task training method—incorporating image classification, image style recognition, and image captioning—to extract modal-shared information and stronger semantics to improve visual representation. We employ task-specific prompts to unify these diverse objectives into a single Masked Language Model (MLM), which serves as the foundation for our Multi-task Supervised Alignment Pre-training (MSAP) framework to enhance the alignment of visual and textual modalities. Extensive experiments on three datasets demonstrate that our method achieves a new state-of-the-art for the FMSA task.